Does supplementation during previous phase influence performance during the growing and finishing phase in Nellore cattle? - Roth, M. T.P.; Resende, F. D. [UNESP]; Oliveira, I. M.; Fernandes, R. M. [UNESP]; Custódio, L. [UNESP]; Siqueira, G. R. [UNESP] (Elsevier, 2017)
In Brazil, the beef cattle are widely raised in pasture post weaning, but the supplementation has been studied only in individual phases of the animal's growth curve. Therefore, the objective of this study was evaluated the nutritional interrelationship between the growing and finishing phases in the performance of Nellore bulls. Eighty-four weaned calves (body weight [BW] = 205 ± 4.7 kg; 8 months) raised on pasture during the growing phase (dry season, summer and autumn) and finished in feedlot were used. The experiment was conducted as a randomized block design with a 2 × 2 × 3 factorial arrangement of treatments. Factors included 1) two supplements levels in the dry season (protein [1 g/kg BW/day - PR1] or protein-energy [3 g/kg BW/day - PE] supplement); 2) two supplement levels in summer (mineral supplement [ad libitum - MS] or protein supplement [1 g/kg BW/day - PR2]); and three supplement levels in autumn (MS, PR2 or PE). The animals were finished with a common diet. The dry season supplementation affected the average daily gain (ADG) in the summer (P < 0.05). In summer, animals fed MS had a greater ADG when fed PR1 in the previous (dry) season than those receiving PE (0.696 vs. 0.581 kg, P < 0.01); while, no difference in ADG was observed when the animals received PR2 (0.815 kg, P = 0.99). In autumn, animals fed PR2 in the previous (summer) season exhibited 11.3% lower ADG than those supplemented with MS (0.503 vs. 0.567 kg, P < 0.01), regardless of the autumn supplementation. Dry season supplementation did not affect the ADG during finishing phase (0.909 kg, P = 0.14). The animals fed PR2 in the summer and PE in the autumn had tendency of lower ADG during the feedlot (P = 0.06) compared with animals fed MS, however, they were finished 20 days earlier (P = 0.06). In conclusion, to provide PE in the dry season, followed by MS in the summer is not recommended, because this strategy reduces the ADG. In addition, dry season supplementation does not affect the ADG during finishing phase, while supply supplements of greater nutritional value in autumn reduces feedlot period.
Keywords: Bos Indicus; Energy; Nutritional strategies; Protein; Tropical grass